Numerical simulation on thermodynamic design model for small-scaled organic rankine cycle with various working fluids - Ng K.; Lim C.W.; Husin N.S.; Abdullah W.S.W.; Eng K.H.; Koh S.P.; Tiong S.K. (American Institute of Physics Inc., 2024)
Organic Rankine cycle (ORC) is one of the solutions for recovering waste heat into useful power output. Low-grade waste heat from various sources can be converted into electricity using ORC in many different aspects. The typical ORC systems in the market often require large amount of waste heat as the waste heat sources. Although the thermal efficiency for marketed ORC is reasonable, it will not be practical in the condition of limited available energy from small-scale waste heat or low temperature heat sources. Hence, this paper presents the numerical simulation of small-scaled ORC using design model developed in MATLAB to study the thermal efficiency of various working fluids in limited working conditions. The fluid properties were obtained from CoolProp library. Result shows that R123 has the highest thermal efficiency of 7.25% with net power output of 4.09kW for this small-scaled ORC. The ranking of refrigerants as working fluids used in the designated working condition is also presented. 2023 Author(s).